Trimester‐specific association of perceived indoor air quality with antenatal depression: China Medical University Birth Cohort Study. (25th November 2022) - Hu, Jiajin; Wan, Ningyu; Ma, Yanan; Liu, Yilin; Liu, Borui; Li, Lin; Liu, Caixia; Qiao, Chong; Wen, Deliang
Abstract: Antenatal depression is associated with adverse birth and long‐term outcomes for mothers and children. Pregnant women spend 90% of time indoors; however, the association between indoor air quality and risk of antenatal depression has not been established. In this study, we aim to determine the total and trimester‐specific association of perceived indoor air quality (PIAQ) with antenatal depression. A total of 2166 pregnant women were enrolled during the first trimester and evaluated during the second and third trimesters in the China Medical University Birth Cohort Study, a prospective pre‐birth cohort study in northeastern China. PIAQ scores were obtained during each of three trimesters, which a higher score indicated a worse indoor air quality. Antenatal depression was screened using an Edinburgh Postnatal Depression Scale (EPDS) and defined as an EPDS score ≥ 9. Prevalence of antenatal depression was 26.7%, 20.6%, and 20.9% during the first, second, and third trimesters, respectively. A higher PIAQ score was positively associated with a depression score throughout pregnancy ( β = 0.27, 95% CI = 0.15–0.39). Trimester‐specific adverse PIAQ exposure was associated with a higher depression score in the same trimester, but not with a higher score in a subsequent trimester. A dose–response pattern and incremental increases in risk of depression were observed with calculated adverse PIAQ exposures across all three trimesters, with the highest risk (OR = 3.24; 95% CI = 2.28–4.78) among women with adverse PIAQ across all three trimesters. The hazardous association between adverse PIAQ exposure and risk of depression were less pronounced among women with higher physical activity levels ( P for interaction < 0.001). The results of present study provided important evidence that pregnant women's mental health was linked to indoor air quality during pregnancy. These findings could be helpful in the development of guidelines to prevent antenatal depression by improving indoor air quality.